OPTIMALISASI PEMBERDAYAAN SUMBER DAYA MANUSIA DALAM LINGKUNGAN BEKERJA - Nusantoro, Eko (Edukasi, 2011)
Through the empowerment of employees, the sharing of power will occur, where the sub-ordinates are collectively involved with the management/chairmen to carry out changes by implementing various managerial approach. A leader of an institution or organization can significantly strengthen the sub-ordinatesÃ¢â¬â¢ self-confidence in their ability. With stronger sense of self of efficacy, the sub-ordinates will be more capable to conduct and succeed in carrying out various challenging jobs. The empowerment should have been pioneered following the globalization era and it needs to create win-win solution situation in an educational institution or organization so that every person will have ability and will have opportunity to be qualified in performance, creative, innovative and maximum self-development in carrying out jobs in their working environment.Kata Kunci: optimalisasi; pemberdayaan SDM; lingkungan kerja